2012
DOI: 10.7836/kses.2012.32.2.001
|View full text |Cite
|
Sign up to set email alerts
|

The Performance and Efficiency Analysis of a PVT System Compared with a PV module and a Solar collector

Abstract: * De p a r t me n to fB i o s y s t e mse n g i n e e r i n g , Ka n g wo nNa t i o n a lUn i v e r s i t y A b s t r a c tA p h o t o v o l t a i c / t h e r ma l ( P VT)s o l a rs y s t e m i st h es o l a rt e c h n o l o g yt h a ta l l o wsf o rs i mu l t a n e o u sc o n v e r s i o no fs o l a r e n e r g yi n t ob o t he l e c t r i c i t ya n dh e a t .Th i sp a p e rc o mp a r e dt h ep e r f o r ma n c eo fP VT s y s t e m wi t hac o n v e n t i o n a lP V mo d u l ea n ds o l a rc o l l e c t o ra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In previous studies, PVT collectors consisted of PV cells throughout the front side [3,5,19]. Also, baffles were fitted inside the collector, mainly to extend the flow path of the heat medium to increase the thermal performance.…”
Section: New Air Pvt Collectormentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, PVT collectors consisted of PV cells throughout the front side [3,5,19]. Also, baffles were fitted inside the collector, mainly to extend the flow path of the heat medium to increase the thermal performance.…”
Section: New Air Pvt Collectormentioning
confidence: 99%
“…Euh et al analyzed the performance and efficiency of a PV, solar thermal collector, and PVT system through experiments. The results showed that the energy storage efficiency of the PVT system was 90.8%, which was the higher than the rate of solar energy storage per unit area than the solar thermal collector (71.5%) and PVs (40.9%) [3]. Jia et al conducted a review on the appropriate environmental conditions and applications for different kinds of PVT systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to analyze PVT systems in comparison with individual PV systems and solar thermal collectors. Euh et al [8] obtained an efficiency for an experimental PVT system without transparent coating that, while it was 13% lower on the thermal side, had 0.8% higher electrical efficiency for electrical conversion compared to the two separate panels. In this way, the total conversion efficiency of the system can be increased by up to 40% [9].…”
Section: Introductionmentioning
confidence: 99%